2021
DOI: 10.1038/s41586-021-03689-8
|View full text |Cite
|
Sign up to set email alerts
|

BANP opens chromatin and activates CpG-island-regulated genes

Abstract: Genotype of cell lines was tested at the level of DNA sequence and protein (Western blotting). Mycoplasma contaminationCell lines tested negative for Mycoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 85 publications
(107 reference statements)
6
76
0
Order By: Relevance
“…So, we first searched for enriched motifs in banp rw337 mutants using a motif discovery software called Hypergeometric Optimization of Motif EnRichment (HOMER) with ATAC-seq data. Consistent with a previous report on human and mouse BANP (Grand et al, 2021), our analysis revealed that TCTCGCGAGA, is the most enriched motif in the closed chromatin region of banp rw337 mutants (Fig. 6A and Fig.…”
Section: Resultssupporting
confidence: 93%
“…So, we first searched for enriched motifs in banp rw337 mutants using a motif discovery software called Hypergeometric Optimization of Motif EnRichment (HOMER) with ATAC-seq data. Consistent with a previous report on human and mouse BANP (Grand et al, 2021), our analysis revealed that TCTCGCGAGA, is the most enriched motif in the closed chromatin region of banp rw337 mutants (Fig. 6A and Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, some specificity in the enrichment was also observed. For example, although p53 and YY motifs were similarly enriched at promoters and enhancers, ETS (promoters vs. enhancers 9.5 versus 2.1 in linear scale) and recently discovered BANP 25 motifs (17.7 versus 2.0) were preferentially, and NRF1 (8.4 versus 1.3) as well as HNF1 motifs (4.3 versus 0.9) almost exclusively enriched at promoters (Fig. 5b,c ).…”
Section: Resultsmentioning
confidence: 84%
“…6d ). On the 5ʹ side, the strongest enrichment occurs close to the TSS, slowly decreasing toward the TATA box; preferential enrichment upstream of the TATA box was also observed for some TFs (e.g., BANP 25 ). On the 3ʹ side, the enrichment declines more sharply with very little motif enrichment observed beyond the +20 position from the TSS (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…CpG islands (CGIs) are generally associated with housekeeping genes (1)(2)(3). BANP, a DNA methylationsensitive CGI binding protein, is required for their activation (4). CGIs are also associated with bivalent genes (5,6), and it is intriguing to ask whether and how CGI-associated bivalent genes are regulated by sequence-specific recognition.…”
mentioning
confidence: 99%